The photocatalytic degradation of methylene blue using bismuth vanadate (Bi2VO5.5) powder - Jitreephan Phanmalee (2018)
© 2017 Trans Tech Publications, Switzerland. Bismuth vanadate (Bi 2 VO 5.5 ) powder has been successfully prepared by microwave method. Bismuth nitrate and ammonium vanadate were used as the starting precursors with the mole ratio of 2:1 in 2-propanol. The microwave power was 500 Watt for 2-6 min. The yellow powder was obtained and calcined at 500°C for 2h. The structure was identified by X-ray diffraction (XRD). The morphology was investigated by field emission scanning electron microscopy (FESEM). The chemical composition was determined by energy dispersive X-ray spectrometry (EDXS). The functional groups were investigated by fourier transform infrared spectrometry (FTIR). The photocatalytic degradation of methylene blue (MB) using Bi 2 VO 5.5 powder was studied by ultraviolet-visible spectrophotometry (UV-Vis).